Analisis Perilaku Pasien Drop Out Pelayanan Fisioterapi Di Rumah Sakit Umum Daerah Arifin Achmad Provinsi Riau - Triyana Triyana; Tri Krianto Karjoso; Agus Alamsyah; Novita Rany; Emy Leonita (STIKes Hang Tuah Pekanbaru, 2021)
The number of drop-out patients of Physiotherapy services at the Arifin Achmad Regional General Hospital in 2019 was 10 percent, while the target is below 5 percent of the 5,079 patients. To achieve the optimal result of physiotherapy, the patient must visit according to schedule. This research aim is to obtain in-depth information about the behavior of drop-out patients of Physiotherapy services at Arifin Achmad regional public hospital. This was a descriptive qualitative study about patients' behavior with a phenomenological design. Research data collection was carried out by in-depth interviews and observations. The number of main informants was 5 people and the supporting informants were 5 people and validated by triangulation. The results showed that the patient’s knowledge about Physiotherapy services was good, the patient’s perception of physiotherapy was good, patient motivation to physiotherapy was good, and the attitude of patients who do not follow a predetermined schedule. The phenomenon that occurs as the patient’s attitudes such as calling a physiotherapist to their home, buying equipment, do-self therapy at home, and move to another hospital nearby that has physiotherapy practice until evening. Advocacy to management was needed setting one man one patient and 2 shift service hours setting, advocacy enabling factors to add Physiotherapy tools, partnerships with first-rate health facilities to improve referral systems.